ELEMEN TANDA DALAM FILM - Arief Agung Suwasono (Institut Seni Indonesia Yogyakarta, 2012)
The film is generally the reconstructed road documentation or representation as the work artisticproduced by the touch art, so that it was able to 'hypnotize' audience that what he saw through rationaldimensions we, as though they were involved in the scope emotional, brought a certain beliefS in thedirection certain, that is not aware is no longer from reality. To the processing narrative and the focalpoint, we will do not understand will participate empathize,feelflush emotion,follow justification in themovie, or even became the inspiration, and believes that his ideology.